AS POLÍTICAS DE PROTEÇÃO SOCIAL E A SEGURANÇA ALIMENTAR: SOBREPESO E OBESIDADE EM ADOLESCENTES BENEFICIÁRIOS DO PROGRAMA BOLSA FAMÍLIA NO MUNICÍPIO DE PONTA GROSSA - PARANÁ - Eickhoff, Gilcéia Luciane Dallagassa (2014)
The current change in the nutritional status of the Brazilian population is characterized by the reduction of malnutrition and the increase in the prevalence of overweight and obesity. Adolescence, not always a healthy lifestyle period, is particularly affected by these changes. Cultural, biological and social aspects may determine a condition of vulnerability, for which policies must address. Thus, strategies for food and nutrition security must occur in a conjugate way in the three levels of power. With regard to food vulnerability, the Bolsa Familia Program - PBF must be highlighted. The study aimed to describe the evolution of policies for food and nutrition security in the city of Ponta Grossa - PR and outline the current nutritional status and determinants in adolescents BFP beneficiaries of Ponta Grossa - PR. A descriptive quantitative research with 313 adolescents aged 10 to 17 years, BFP beneficiaries studying in public schools was held. Socioeconomic conditions have been raised through a questionnaire administered to parents. In order to assess the nutritional status of the adolescents, a questionnaire used in National Survey of School Health - PeNSE - 2009 was applied and anthropometric data, such as age, weight, height and waist circumference was collected. Nutritional status was classified according to the World Health Organization, and data interpretation of waist circumference used parameter proposed by Fernández (2004). Most parents lies in the range 31-48 years, with predominance of social class C2 (42.4%) and family income between 251 and 500 reals. On mothers, 60% were illiterate or had only the first stage of basic education. Approximately 50% of households are headed by his father and about 40% for the mother. 15% of families have more than two residents per bedroom, and the average number of residents per household was 3.79%. The nutritional status, in general, proved to be better than that observed in the rest of Paraná state or even the country, a fact verified by the lower rate of overweight and lower consumption of unhealthy foods. Girls had a higher prevalence of overweight and obesity, with 36.7% not practicing physical activities. The TV is the electronic equipment with higher daily usage time, adding more than 7 hours daily. Social policies of the federal, state and municipal governments coexist in the city, collaborating, possibly for the current existing status. Despite the possible biases and being a cross-sectional study, the results can be evidence of the effectiveness of policies, although studies with more complex designs are necessary.